Efficacy of preoperative transcutaneous electrical acupoint stimulation in reducing postoperative delirium in older adults undergoing orthopedic surgery: a randomized controlled trial - Sun, Long; Ruan, Wen-Qing; Zou, Ying-Hua; Wei, Pan; Li, He; Wang, Yong-Qiang; Li, Xing; Song, Jian-Gang (Frontiers in Neurology, 2025)
BackgroundPostoperative delirium (POD) is a common complication. Pain and sleep disturbances may contribute to the development of postoperative delirium, while transcutaneous electrical acupoint stimulation (TEAS) can alleviate these symptoms. This study investigated the effect of preoperative TEAS on POD prevention in older patients undergoing orthopedic surgery.MethodsA total of 608 patients were randomly assigned to either an intervention group (TEAS group) or a placebo group (control group). The TEAS group received stimulation at bilateral Hegu–Neiguan and Zusanli–Taichong acupoints for three consecutive days prior to surgery. POD was assessed twice daily using the Confusion Assessment Method from postoperative day 1 through day 5. Sleep disturbances were evaluated using the Athens Insomnia Scale (AIS), and pain was measured using the visual analog scale (VAS) on preoperative 3 days. Serum levels of interleukin-6 (IL-6), C-reactive protein (CRP), and S100β protein were quantified on postoperative days 1 and 3. In addition, cognitive function was evaluated on postoperative day 7 using the Montreal Cognitive Assessment (MoCA).ResultsThe incidence of POD was significantly lower in the TEAS group compared to the control group (6.08% vs. 17.57%, p < 0.001). Patients in the TEAS group also exhibited significantly lower serum levels of IL-6, CRP, and S100β on both postoperative days 1 and 3 (p < 0.05). Furthermore, significant improvements were observed in preoperative AIS scores and VAS scores for pain on days 1 and 2 prior to surgery in the TEAS group compared to the control group (p < 0.05). Besides, the MoCA score in the TEAS group was significantly higher than in the control group on postoperative day 7 (p < 0.05).ConclusionPreoperative application of TEAS was associated with a reduced incidence of POD in older adults undergoing orthopedic surgery. The intervention may also contribute to improvements in preoperative sleep quality and pain reduction, as well as attenuation of postoperative inflammatory responses.Clinical trial registrationThe trial was prospectively registered with the Chinese Clinical Trial Registry (Registration No. ChiCTR-INR-17012951; October 12, 2017).